Problem-based Learning in English Teaching: A Systematic Literature Review - Heppy Mutammimah; Padli Padli (Universitas Muhammadiyah Semarang, 2023)
The industrial revolution 4.0 brought many changes in various sectors of life, including education. It also impacts curriculum changes. In the latest curriculum, MBKM, one of its characteristics is student-centered learning with one of its methods, namely case-based learning or problem-based learning. This study aims to find out how deep and extensive research has been conducted between 2013-2023 regarding problem-based learning in English teaching and the issues that develop in it. To reach those aims, the researchers use the Systematic Literature Review (SLR) method and Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) as a data collection and reporting protocol. The findings revealed a noticeable increase in publications emphasizing problem-based learning as the main focus in the last three years. Among the numerous publications reviewed, the majority consisted of quantitative research studies. The research subjects predominantly comprised college and undergraduate students, while the most frequently chosen topic was problem-based learning in teaching writing. This comprehensive finding will reveal publishers, authors, research methods, issues, gaps, and novelties in problem-based Learning research that researchers can use for future research.